2020
DOI: 10.1200/jco.2020.38.15_suppl.8503
|View full text |Cite
|
Sign up to set email alerts
|

Idecabtagene vicleucel (ide-cel; bb2121), a BCMA-targeted CAR T-cell therapy, in patients with relapsed and refractory multiple myeloma (RRMM): Initial KarMMa results.

Abstract: 8503 Background: Outcomes are poor in triple-class exposed RRMM patients (pts) who progress on immunomodulatory agents (IMiDs), proteasome inhibitors (PIs), and CD38 antibodies (mAbs). Ide-cel, a BCMA targeted CAR T cell therapy, showed promising tolerability and efficacy in RRMM pts in the phase I CRB-401 study ( NEJM2019;380:1726). We present primary efficacy and safety data from the pivotal phase II KarMMa trial of ide-cel in RRMM (NCT03361748). Methods: Enrolled pts had ≥3 prior regimens (including IMiD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 0 publications
6
93
0
1
Order By: Relevance
“…The median OS was 19.4 months (95% CI, 18.2-NE). In this study, peak CAR T-cell expansion did correlate with clinical outcome, and cell expansion correlated with longer PFS in the higher dose levels [23].…”
Section: Clinical Data Using Car T-cells In MMsupporting
confidence: 47%
See 1 more Smart Citation
“…The median OS was 19.4 months (95% CI, 18.2-NE). In this study, peak CAR T-cell expansion did correlate with clinical outcome, and cell expansion correlated with longer PFS in the higher dose levels [23].…”
Section: Clinical Data Using Car T-cells In MMsupporting
confidence: 47%
“…CAR-T cell expansion and peak CAR-T cell levels do correlate with response across different trials [28,30,33]. In the KarMMa [23] study, peak ide-cel vector copies were significantly higher in responders as compared to non-responders, and a similar experience was published with the UPenn BCMA CAR T-cell [30]. However, recent data using cilta-cel in the phase 1b/2 CARTITUDE-1 study fail to show this correlation.…”
Section: Peak Expansion and Responsementioning
confidence: 91%
“…One hundred seven (83.6%) patients encountered CRS including 7 (5.5%) grade ≥ 3 events and 1 death. Twenty-three (18%) patients encountered NTX including 4 (3.1%) grade ≥ 3 events [103].…”
Section: Car-bcmamentioning
confidence: 99%
“…The first results with bb2121, from the phase 1 study CRB 401, showed an ORR of 85% with 45% CR in end-stage RRMM patients and a median PFS of 11.8 months [ 41 ]. These results led to the development of a phase 2 study, KarMMa1 [ 42 ]; most of the patients were heavily pre-treated (median of six previous treatments) and 84% were triple-class (IMiD, PI, anti-CD38 mAb) refractory. The ORR was 73%, including 33% CR, and median PFS was 8.8 months.…”
Section: Relapse or Refractory Multiple Myelomamentioning
confidence: 99%